2009
DOI: 10.1158/0008-5472.can-09-2236
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in Processing of mRNA 3′ Untranslated Regions Characterize Clinically Distinct Cancer Subtypes

Abstract: Molecular cancer diagnostics are an important clinical advance in cancer management, but new methods are still needed. In this context, gene expression signatures obtained by microarray represent a useful molecular diagnostic. Here, we describe novel probe-level microarray analyses that reveal connections between mRNA processing and neoplasia in multiple tumor types, with diagnostic potential. We now show that characteristic differences in mRNA processing, primarily in the 3′-untranslated region, define molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
129
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 48 publications
10
129
0
3
Order By: Relevance
“…As DNA repair proceeds, the levels of p53 expression decrease allowing the recovery of total mRNA levels. Our results indicate that different cell lines exhibit different 3 0 processing profiles depending on p53 expression levels, consistent with the idea proposed by Singh et al (2009) that the interaction of the 3 0 processing machinery and factors involved in the DDR/ tumor suppression might result in cell-specific 3 0 processing profiles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As DNA repair proceeds, the levels of p53 expression decrease allowing the recovery of total mRNA levels. Our results indicate that different cell lines exhibit different 3 0 processing profiles depending on p53 expression levels, consistent with the idea proposed by Singh et al (2009) that the interaction of the 3 0 processing machinery and factors involved in the DDR/ tumor suppression might result in cell-specific 3 0 processing profiles.…”
Section: Discussionsupporting
confidence: 90%
“…Other tumor suppressors, such as CSR1 and Cdc73, have also been shown to functionally associate with 3 0 processing factors, such as CPSF3 (Zhu et al, 2009) and CPSF/ CstF (Rozenblatt-Rosen et al, 2009). Recently, it has been shown that the use of alternative mRNA 3 0 cleavage and polyadenylation sites can control the expression of certain genes by eliminating or including several cis-acting elements, such as microRNA target sites and AU-rich elements, in cancer cells and during development (Sandberg et al, 2008;Zlotorynski and Agami, 2008;Ji et al, 2009;Mayr and Bartel, 2009;Singh et al, 2009). Although more work is necessary to determine the functional relevance of the CstF/BARD1/ p53 interaction in the regulation of expression of specific genes involved in DDR, it is possible that the p53-mediated inhibition of mRNA 3 0 processing might also play a role in the selection of different alternative mRNA 3 0 cleavage sites and, consequently, in the regulation of the mRNA levels of genes involved in DDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cis-acting elements within the 3' untranslated region (3'UTR), such as APA signals, microRNA (miRNA) target sites and AU-rich elements (ARE), play also an important role regulating 3' processing. The relevance of these regulatory processes is highlighted by changes in the length of the 3'UTR of different mRNAs in cancer cells 10,11 and during cell differentiation. [12][13][14] For better understanding of basic aspects of 3' end formation and its regulation, we suggest the reading of a recent review by Mandel et al 5 As no mechanism has been described yet that regulates the length of the poly(A) tail during the nuclear cleavage/polyadenylation reaction, it is easy to view this modification as a default mRNA processing step.…”
Section: Nuclear Polyadenylation/ Deadenylationmentioning
confidence: 99%
“…Although a direct connection between APA and the polyadenylation/ deadenylation machinery has not been described, the selection between the distal or proximal alternative signals might cause the inclusion or exclusion of other cis-acting RNA elements involved in polyadenylation/deadenylation processes. The relevance of these regulatory processes is highlighted by the finding of changes in the length of the 3'UTRs of different mRNAs, which change the number of miRNA target sites and AREs, in cancer cells 10,11 and during cell differentiation. [12][13][14] miRNAs comprise a large family of small single-stranded non-coding RNAs (~21 nts in length), which are encoded within the genome of species ranging from protozoans to plants to mammals.…”
Section: Cis-elements Involved In Polyadenylation/deadenylationmentioning
confidence: 99%